Disiplin Bidan Dalam Pencatatan dan Pelaporan Pemantauan Wilayah Setempat Kesehatan Ibu dan Anak (PWS-KIA) di Puskesmas Kabupaten Sukabumi: Discipline of Midwives in Recording and Reporting Monitoring of Local Areas of Maternal and Child Health (PWS-KIA) at Puskesmas Sukabumi Regency - Mulya, Alis (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: The lack of competent human resources in data management is also a factor that results in weak recording and reporting systems, especially in terms of data management, including in the PWS KIA system. Methods: The method used in this study is a quantitative approach that uses a cross-sectional design. The sample used was 70 midwives as respondents. The analytical method used is the Structural Equation Model (SEM) using SmartPLS 2.0 and SPSS 20. Results: The results showed the work climate variables (24.91%), workload (10.93%), and work motivation (10.55%). The direct influence of the discipline of Midwives in the Sukabumi District Health Center was 77.1% and indirect effects were 0.35%. Discussion: Leaders should provide positive support for their career development, provide broad opportunities to develop themselves, listen and pay attention to natural difficulties, not always blame, let alone apply discriminatory consequences of conflict.